Makna dan Nilai Kearifan Lokal Pada Tradisi Mallasuang Manu’ Masyarakat Mandar di Kabupaten Kotabaru - Izzah, Nurul; Budhi, Setia (Prodi Sosiologi FISIP ULM, 2024)
Mallasuang Manu tradition is a ceremony of releasing a pair of chickens to be fought over by the community as a gratitude for the abundance of sea and land products which has a purpose as a ritual for local young people as a form of request to God Almighty to get a mate. The purpose of this research is to reveal the meaning in the mallasuang manu tradition. This research uses a qualitative approach. The data collection process was carried out by means of field research through participant observation, in-depth interviews and documentation. Data analysis was conducted using an interactive model, which consists of data collection, data reduction, data presentation and conclusion drawing/verification. The theory used is Herbert Blumer's symbolic interactionism. The results showed that the Mallasuang Manu' tradition is a tradition that is full of meaning. The meaning in this tradition is formed through a series of social interaction processes and meaning adjustments so that it can form a set of values, norms, rules and beliefs. The Mallasuang Manu' tradition is a local wisdom culture typical of the Mandar tribe as a result of the creation, taste and culture of the Mandar people. As local wisdom, the mallassuang manu tradition has values that contain philosophical meanings of the way of life. The meaning of morality of relationships between people manifested in mutual cooperation, the meaning of gratitude to God Almighty manifested in spiritual values, obedience, harmony, unity and unity manifested in cultural values. The conclusion is that the mallasuang manu tradition is a tradition that has been carried out for generations and is a condition of local wisdom that continues to be preserved by the people of Teluk Aru Village. It is hoped that this tradition can be further developed and managed properly as a traditional tourism asset of Kotabaru Regency, especially Teluk Aru Village.